PENGARUH EFIKASI DIRI DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PT ASIA TRITUNGGAL JAYA - Taufik Muhamad Riyadi (SECAD, 2025)
This study aims to determine and analyze the influence of self-efficacy and organizational culture on employee performance at PT Asia Tritunggal Jaya, both simultaneously and partially. The research method used is a survey method with data collection techniques through interviews, questionnaires, and documentation studies. The population consisted of 251 employees of PT Asia Tritunggal Jaya, with a sample of 155 respondents selected through random sampling. The analysis technique used in this study is path analysis. The results of this study indicate that both partially and simultaneously, the variables of self-efficacy and organizational culture have a positive and significant effect on employee performance at PT Asia Tritunggal Jaya.